Wire preparation method of copper-based composite material

The reinforced phase is uniformly distributed in the copper matrix through the friction stir extrusion process, solving the problem of uneven dispersion of the second phase particles in the copper-based composite material, realizing the preparation of high-performance copper-based composite wire, significantly improving the strength and plasticity of the material, and is suitable for a variety of high-performance applications.

CN120079861APending Publication Date: 2025-06-03CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510292058.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

In the preparation of existing copper-based composite materials, the second phase particles are unevenly dispersed, resulting in uneven material properties, and the problems of thermal cracks, surface roughness and difficult to control dimensional accuracy are prone to occur during the wire forming process.

Method used

The new friction stir extrusion process is adopted to cut the reinforced phase and evenly distribute it in the copper matrix. Materials with different properties are flexibly prepared by adjusting the proportion of the second phase in the silo, and by precisely controlling the diameter and process parameters of the wire material, high-precision molding of micron-sized diameter wire material is achieved.

Benefits of technology

It effectively solves the problem of uneven dispersion of second phase particles, significantly improves the strength and plasticity of the material, avoids thermal cracks and surface defects, and realizes the preparation of high-performance copper-based composite wires, which are suitable for key components such as high-frequency signal transmission cables, antenna components, and electrical connection lines of aerospace vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120079861A_ABST
    Figure CN120079861A_ABST
Patent Text Reader

Abstract

The invention relates to a wire preparation method of a copper-based composite material, belongs to the technical field of material science and engineering, and particularly relates to a preparation and processing technology of a high-performance metal material. On the basis of a novel friction stirring extrusion process, a strengthening phase is sheared and uniformly dispersed and distributed in a copper matrix through the friction stirring effect, the problem that second-phase particles are not uniformly dispersed is solved, meanwhile, the diameter of the wire can be accurately controlled, controllable preparation of the copper-based composite wire with the micron-sized diameter is achieved, and the production cost is reduced. And hot cracks and surface defects in a traditional process are avoided, the strength and plasticity of the material are remarkably improved, and the requirement for the copper-based composite wire in the high-performance field is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a wire of a copper-based composite material, belonging to the technical field of materials science and engineering, and specifically relating to the preparation and processing technology of high-performance metal materials. Background Art

[0002] Copper-based alloys and composite materials have broad application prospects in high-tech fields due to their excellent electrical conductivity, thermal conductivity, mechanical properties, and corrosion resistance. In the high-speed rail field, copper-based alloy wires can be used for key components such as traction motor windings, catenary conductors, and signal transmission cables. Their high electrical conductivity and excellent mechanical properties can significantly improve the operating efficiency and safety performance of high-speed rails, while extending the service life of components and reducing maintenance costs. In the communication field, with the rapid development of 5G and future higher-frequency communication technologies, higher requirements are put forward for the electrical conductivity and electromagnetic interference resistance of signal transmission materials. However, there are still many technical problems in the preparation of copper-based composite materials, especially in the wire forming process, which limit their further application in high-performance fields.

[0003] Firstly, in the preparation process of traditional copper-based composite materials, it is difficult to ensure the uniform dispersion of the second-phase particles, which easily leads to non-uniform material properties and affects their mechanical properties and electrical conductivity. Secondly, during the wire forming process, due to the high thermal conductivity and low strength of copper-based materials, problems such as thermal cracks, rough surfaces, and difficult control of dimensional accuracy are likely to occur, especially when forming thin wires, these problems are particularly prominent. These technical bottlenecks severely restrict the application of copper-based alloys and composite materials in fields such as high-speed rail, communication, aerospace, etc. Solving the above problems will be beneficial to the high-quality preparation of key components applicable to high-frequency signal transmission cables, antenna components, and base station connection lines, and can effectively improve the transmission efficiency and stability of communication equipment. In the aerospace field, copper-based alloy wires can be widely used for key components such as electrical connection wires, sensor wires, and thermal management systems of aircraft and spacecraft due to their high temperature resistance, corrosion resistance, and fatigue resistance in extreme environments, providing an important guarantee for the reliability and safety of aircraft and spacecraft.

[0004] Currently, the main methods for preparing copper wires include drawing, extrusion, electrodeposition, powder metallurgy, etc. The drawing method is the most commonly used method, with mature technology, low cost and high production efficiency. However, there are problems such as limited material properties, poor surface quality and difficulty in preparing ultra-fine copper wires. The extrusion method can prepare copper wires with better density, especially suitable for composite materials, but the equipment is complex, the cost is high and the process control is difficult, and there are great difficulties in preparing wire materials with micron-level diameters. The electrodeposition method can prepare high-precision micron-level or even nano-level copper wires with good surface quality, but the production efficiency is low, the cost is high and the mechanical properties of the materials are poor. The powder metallurgy method is suitable for preparing copper-based composite materials with controllable material properties, but the process is complex, the cost is high and the material density is poor. The existing process methods generally have problems such as uneven dispersion of second-phase particles, difficulty in forming fine wires, difficulty in balancing strength and plasticity, and complex processes and high costs. Summary of the Invention

[0005] In view of the above problems, based on the new friction stir extrusion process, the present invention develops a method for preparing copper-based composite material wires suitable for high-performance requirements. Through the friction stir action, this process shears and evenly disperses the strengthening phase in the copper matrix, thus effectively solving the problem of uneven dispersion of second-phase particles. At the same time, by adjusting the proportion of the second phase in the hopper, copper-based composite materials with different second-phase composites can be flexibly prepared to meet diverse performance requirements. In addition, this process can precisely control the diameter of the wire, realizing the controllable preparation of micron-level diameter wire materials, avoiding the generation of thermal cracks and surface defects in traditional processes, and significantly improving the strength and plasticity of the materials. The present invention not only solves the technical problems in the wire forming of copper-based alloys and composite materials, but also promotes their application in high-performance fields, providing important material support for the technological progress and industrial upgrading of related industries, and having significant practical application value and broad market prospects.

[0006] Based on the new friction stir extrusion process, the present invention shears and evenly disperses the strengthening phase in the copper matrix through the friction stir action, solves the problem of uneven dispersion of second-phase particles, and at the same time can precisely control the wire diameter, realizing the controllable preparation of micron-level diameter copper-based composite material wires, avoiding thermal cracks and surface defects in traditional processes, and significantly improving the strength and plasticity of the materials, meeting the requirements of high-performance fields for copper-based composite material wires.

[0007] The present invention relates to a method for preparing copper-based composite material wires, comprising the following steps:

[0008] Step 1

[0009] After taking and mixing copper source particles and reinforcing phase particles according to the designed composition ratio and uniformly mixing them, they are pressed into shape to obtain a preform with a preform density ≥ 70% of the theoretical density;

[0010] Step 2

[0011] Add the obtained preform into a silo and prepare a wire by friction stir extrusion process;

[0012] When preparing the wire by friction stir extrusion process, set the initial rotational speed of the grinding head to 30 - 60 rpm / min, and keep the rotational speed after contacting with the raw materials in the silo, so that the temperature of the grinding head gradually rises to A °C; during the preheating stage of the grinding head, the pressure applied by the hydraulic system is 0.2 - 0.7 MPa to ensure that the initial pressure when the grinding head contacts the raw materials is appropriate, avoiding premature deformation or extrusion of the materials; the value of A is 180 - 230; when the preheating temperature of the grinding head reaches A °C, start the stagewise temperature increase,

[0013] First stage temperature increase: Increase the rotational speed of the grinding head to 100 - 150 rpm / min to raise the grinding surface temperature to 350 - 400 °C; during this stage, the hydraulic pressure is maintained at 0.2 - 0.7 MPa to ensure a uniform temperature rise; Second stage temperature increase: Increase the rotational speed of the grinding head again to 150 - 200 rpm / min to raise the grinding surface temperature to 450 - 600 °C; if in the composite material, the alloy used has a recrystallization temperature, then the second stage temperature increase can be to 30 - 50 °C lower than the recrystallization temperature;

[0014] The above temperatures can achieve the effect of grain refinement,

[0015] During this stage, the hydraulic pressure is gradually increased to 1 - 3 MPa to ensure that the material has good plastic fluidity at high temperatures;

[0016] Step Three

[0017] Cool the wire prepared by friction stir extrusion process at a cooling rate greater than 50 K / s to obtain the product.

[0018] The raw materials of the present invention can be various copper alloy powders, scraps, ingots, etc., and the composite materials can be various reinforcing phase particles from nanometer to micrometer scale (such as ceramic particles, carbon nanotubes, graphene, etc.). The selection of the composite phase should be specified according to the performance requirements of the final material. For example, graphene or carbon nanotubes can be selected to enhance the conductivity; ceramic particles such as silicon carbide or alumina can be selected to enhance the mechanical properties; hard particles such as tungsten carbide or silicon nitride can be selected to enhance the wear resistance.

[0019] In the present invention, the particle size of the reinforcing phase particles is nanoscale and / or micrometer scale.

[0020] The reinforcing phase particles are selected from at least one of oxide ceramic particles, carbon nanotubes, graphene, hard particles, and high-temperature reinforcing phases.

[0021] Preferably, the mass of the reinforcing phase particles accounts for 10% or less of the mass of the copper-based composite material.

[0022] In the present invention, in order to achieve uniform mixing of the raw materials of the copper-based composite material, the mixing process used is selected from at least one of mechanical mixing method, high-energy ball milling method, gas flow mixing method, wet mixing method, and electrostatic mixing method.

[0023] Preferably, the mechanical mixing method is as follows: using a V-type mixer or a double-cone mixer, mixing copper powder and reinforcing phase particles in proportion, and controlling the mixing time within 1 to 2 hours to ensure uniform dispersion of the powder;

[0024] Preferably, the high-energy ball milling method is as follows: using a high-energy ball mill, loading copper powder and reinforcing phase particles into the ball milling tank in proportion, adding grinding balls, controlling the ball milling time within 4 to 8 hours, and the ball milling speed at 200 to 400 rpm to ensure uniform mixing of the powder and achieve mechanical alloying;

[0025] Preferably, the gas flow mixing method is as follows: using a gas flow mixing device, loading copper powder and reinforcing phase particles into the device in proportion, and making the powder suspended and mixed by high-speed gas flow, controlling the mixing time within 10 to 30 minutes to ensure uniform dispersion of the powder.

[0026] In the present invention, the pressing and forming is selected from at least one of dry pressing, wet pressing, cold isostatic pressing, hot isostatic pressing, injection molding, and extrusion molding.

[0027] Preferably, the dry pressing is as follows: loading the mixed powder into a mold, and pressing it at room temperature using a hydraulic press, controlling the pressure within 200 to 400 MPa, and the density of the pressed green body ≥ 70% of the theoretical density.

[0028] Preferably, the wet pressing is as follows: mixing the mixed powder with a binder (such as polyvinyl alcohol) to form a slurry, then injecting it into a mold, and pressing it at room temperature using a hydraulic press, controlling the pressure within 100 to 200 MPa, and the density of the pressed green body ≥ 70% of the theoretical density.

[0029] Preferably, the cold isostatic pressing is as follows: loading the mixed powder into a rubber mold, and pressing it at room temperature using a cold isostatic pressing device, controlling the pressure within 200 to 300 MPa, and the density of the pressed green body ≥ 70% of the theoretical density.

[0030] Preferably, the hot isostatic pressing is as follows: loading the mixed powder into a mold, and pressing it at high temperature (500 to 800 °C) and high pressure (100 to 200 MPa) using a hot isostatic pressing device, and the density of the pressed green body ≥ 90% of the theoretical density.

[0031] Preferably, the material of the feed bin should be selected as hot work die steel, preferably H13 steel, to ensure good wear resistance and thermal stability at high temperature.

[0032] The ratio of the diameter of the center hole of the grinding head to the target wire diameter is 0.75 to 0.9, preferably 0.8 to 0.88, and the diameter of the center hole of the grinding head is greater than the maximum size of the reinforcing phase particles in three-dimensional space.

[0033] Preferably, the extruded wire should be rapidly cooled to prevent grain coarsening and oxidation. The inert gas air cooling method can be used, and the cooling rate is controlled at 10 2 ~10 4 K / s.

[0034] By optimizing the material composition design and preparation process, the present invention develops a method for preparing copper-based alloy or composite material wire suitable for high-performance requirements, which can effectively solve the problems of uneven dispersion of the second-phase particles and difficulty in forming fine wires in the traditional process.

[0035] Through the friction stir action, the present invention shears and evenly disperses the strengthening phase in the copper matrix, solving the problem of uneven dispersion of the second-phase particles in the traditional process. By precisely controlling the diameter of the center hole of the grinding head and the extrusion pressure, high-precision forming of micron-sized diameter wires is achieved, solving the problem of difficulty in forming fine wires in the traditional process. By optimizing process parameters such as rotational speed, temperature, and extrusion pressure, the strength and plasticity of the material are significantly improved.

[0036] Beneficial effects

[0037] The present invention provides a method for preparing copper-based alloy or composite material wire. Compared with the prior art, it has the following significant advantages:

[0038] Through the friction stir action, the present invention shears and evenly disperses the strengthening phase in the copper matrix, solving the problem of uneven dispersion of the second-phase particles in the traditional process and avoiding the problem of uneven performance caused by particle agglomeration in the traditional process.

[0039] By precisely controlling the extrusion pressure in cooperation with the diameter of the center hole of the grinding head, high-precision forming of micron-sized wires is achieved. The forming accuracy of the fine wires is high, and the surface quality is good, avoiding the problems of difficulty in forming fine wires and rough surfaces in the traditional process, and is particularly suitable for the preparation of micron-sized diameter wires.

[0040] The present invention adopts the friction stir extrusion process and uses frictional heat to heat the material, reducing the energy consumption of external heat sources. Compared with the traditional melting and extrusion processes, the energy consumption is reduced by 20% to 30%, significantly reducing the production cost. And by precisely controlling the extrusion speed and temperature, efficient continuous production is achieved. The production rate is increased by 15% to 25%, and it is particularly suitable for large-scale production. Description of the drawings

[0041] Figure 1 It is the design drawing of the friction extrusion equipment;

[0042] Figure 2 Field picture of preparing copper-graphene composite wire by the friction extrusion equipment in Example 1;

[0043] Figure 3 Cross-section transmission characterization and energy spectrum diagram of the product obtained in Example 1;

[0044] Figure 4 Tensile mechanical property curve of the sample in Example 1;

[0045] Figure 5 Photo of the discontinuous wire feeding sample in Comparative Example 1. Detailed implementation manners

[0046] Example 1

[0047] First, prepare copper powder with a purity of 99.7% (particle size 30 - 70 μm) and graphene with a purity of 99.6% (diameter 100 - 150 nm, thickness 1 - 2 nm) as the reinforcement phase, mix them in a mass ratio of 97:3, and use the wet mixing process to mix the powder with ethanol to form a suspension. Ultrasonically disperse for 30 minutes to ensure uniform dispersion of the powder. Subsequently, inject the mixed slurry into a mold and press it at room temperature with a pressure of 150 MPa using a hydraulic press to prepare a preform with a density ≥ 70% of the theoretical density. Next, perform the extrusion process using a friction stir extruder equipped with an H13 steel hopper: set the initial rotational speed of the grinding head to 60 rpm / min, preheat to 220 °C, and the hydraulic pressure is 0.6 MPa; then increase the temperature in two stages. In the first stage, increase the rotational speed to 150 rpm / min to raise the grinding surface temperature to 450 °C, and in the second stage, increase the rotational speed to 200 rpm / min to raise the grinding surface temperature to 600 °C. At an extrusion temperature of 600 °C, perform friction extrusion with an extrusion pressure of 5 MPa and an extrusion speed of 12 mm / min. Protect the wire outlet end with argon (flow rate 6 L / min), and design the diameter of the central hole of the grinding head to be 5 μm to prepare a wire with a target diameter of 6 μm. The extruded wire is rapidly cooled through a water cooling system at a speed of 10 4 K / s to obtain a graphene-reinforced copper alloy composite wire, and its extrusion process is as Figure 2 shown. Figure 3 Characterization results of the graphene-reinforced wire. The scanning electron microscope results show that graphene has been uniformly distributed in the copper matrix. The transmission electron microscope results show that the size of the graphene reinforcement phase introduced through the friction extrusion process is below 50 nm and is uniformly and dispersedly distributed in the matrix; no wire breakage phenomenon is observed during continuous preparation of 2 meters.

[0048] Example 2

[0049] First, prepare copper powder with a purity of 99.8% (particle size 20 - 60 μm) and alumina particles with a purity of 99.7% (particle size 1 - 3 μm) as the reinforcement phase. Mix them in a mass ratio of 90:10 and use an air flow mixing device to mix under high-speed air flow for 30 minutes to ensure uniform dispersion of the powder. Subsequently, load the mixed powder into a rubber mold and use a cold isostatic pressing device to press at a pressure of 250 MPa at room temperature to prepare a preform with a density ≥ 75% of the theoretical density. Next, perform an extrusion process using a friction stir extruder equipped with an H13 steel hopper: set the initial rotational speed of the grinding head at 40 rpm / min, preheat to 180 °C, and the hydraulic pressure is 0.4 MPa; then raise the temperature in two stages. In the first stage, increase the rotational speed to 100 rpm / min to raise the grinding surface temperature to 350 °C, and in the second stage, increase the rotational speed to 160 rpm / min to raise the grinding surface temperature to 530 °C. At an extrusion temperature of 530 °C, perform friction extrusion at an extrusion pressure of 3 MPa and an extrusion speed of 8 mm / min, and use helium protection at the wire outlet end (flow rate 4 L / min), and rapidly cool at a speed of 10 3 K / s. The diameter of the central hole of the grinding head is designed to be 3 μm, and a copper-based composite material wire with a target diameter of 3.5 μm is prepared. Continuous preparation of 1 m shows no wire breakage phenomenon).

[0050] Comparative Example 1

[0051] First, prepare copper powder with a purity of 99.8% (particle size 15 - 120 μm) and alumina particles with a purity of 99.7% (particle size 1 - 3 μm) as the reinforcement phase. Mix them in a mass ratio of 80:20 and use an air flow mixing device to mix under high-speed air flow for 30 minutes to ensure uniform dispersion of the powder. Subsequently, load the mixed powder into a rubber mold and use a cold isostatic pressing device to press at a pressure of 250 MPa at room temperature to prepare a preform with a density of 60% of the theoretical density. Next, perform an extrusion process using a friction stir extruder equipped with an H13 steel hopper: set the initial rotational speed of the grinding head at 100 rpm / min to raise the grinding surface temperature to 350 °C, and in the second stage, increase the rotational speed to 160 rpm / min to raise the grinding surface temperature to 530 °C. At an extrusion temperature of 530 °C, perform friction extrusion at an extrusion pressure of 3 MPa and an extrusion speed of 10 mm / min, and use helium protection at the wire outlet end (flow rate 4 L / min), and rapidly cool at a speed of 10 3 K / s. The diameter of the central hole of the grinding head is designed to be 3 μm, and a copper-based composite material wire with a target diameter of 3.5 μm is prepared. The wire is discontinuous ( Figure 5 )

Claims

1. A method for preparing a copper-based composite material wire, characterized in that: The steps include: Step 1 Copper source particles and reinforcement phase particles are taken according to the designed composition and mixed evenly, and then pressed into shape to obtain a blank with a blank density ≥ 70% of the theoretical density; Step 2 The obtained blank is added into a silo, and the wire is prepared by a friction stirring extrusion process; When preparing wire by friction stir extrusion process, the initial speed of the grinding head is set to 30-60 rpm / min, and the speed is maintained after contacting with the raw materials in the silo, so that the temperature of the grinding head gradually increases to A℃; in the preheating stage of the grinding head, the pressure applied by the hydraulic system is 0.2-0.7 MPa, and the value of A is 180-230; when the preheating temperature of the grinding head reaches A℃, the staged heating begins. The first stage of heating: increase the grinding head speed to 100~150 rpm / min, so that the grinding surface temperature rises to 350~400℃; the hydraulic pressure in this stage is maintained at 0.2~0.7 MPa; the second stage of heating: increase the grinding head speed to 150~200 rpm / min again, so that the grinding surface temperature rises to 450~600℃; if the alloy used in the composite material has a recrystallization temperature, the temperature in the second stage can be raised to 30~50℃ lower than the recrystallization temperature; the hydraulic pressure in the second stage is gradually increased to 1~3 MPa; Step 3 The wire prepared by the friction stir extrusion process is cooled at a cooling rate greater than 50K / s to obtain a product.

2. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The particle size of the reinforcement phase particles is nanometer-scale and / or micrometer-scale.

3. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The reinforcing phase particles are selected from at least one of ceramic particles, carbon nanotubes, graphene, and hard particles; The mass of the reinforcement phase particles accounts for 10% or less of the mass of the copper-based composite material.

4. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The mixing process used is selected from at least one of mechanical mixing, high-energy ball milling, air flow mixing, wet mixing and electrostatic mixing.

5. The method for preparing a copper-based composite material wire according to claim 4, characterized in that: The mechanical mixing method is: using a V-type mixer or a double cone mixer, the copper powder and the reinforcement phase particles are mixed in proportion, and the mixing time is controlled within 1 to 2 hours to ensure that the powder is evenly dispersed; The high-energy ball milling method comprises: using a high-energy ball mill, placing copper powder and reinforcement phase particles into a ball milling jar in proportion, adding grinding balls, controlling the ball milling time to 4 to 8 hours, and the ball milling speed to 200 to 400 rpm to ensure that the powders are evenly mixed and mechanical alloying is achieved; The airflow mixing method uses an airflow mixing device to load copper powder and reinforcing phase particles into the device in proportion, suspend and mix the powders through high-speed airflow, and control the mixing time to 10 to 30 minutes to ensure uniform dispersion of the powders.

6. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The pressing molding is selected from at least one of dry pressing molding, wet pressing molding, cold isostatic pressing, hot isostatic pressing, injection molding, and extrusion molding.

7. The method for preparing a copper-based composite material wire according to claim 6, characterized in that: The dry pressing molding comprises: loading the mixed powder into a mold, using a hydraulic press to press at room temperature, controlling the pressure at 200-400 MPa, and the density of the pressed blank is ≥70% of the theoretical density; The wet pressing molding comprises: mixing the mixed powder with the binder to form a slurry, injecting the slurry into a mold, and pressing the slurry at room temperature using a hydraulic press, with the pressure controlled at 100-200 MPa, and the density of the preform after pressing being ≥70% of the theoretical density; The cold isostatic pressing molding comprises: loading the mixed powder into a rubber mold, using a cold isostatic pressing device to press at room temperature, the pressure being controlled at 200-300 MPa, and the density of the preform after pressing being ≥70% of the theoretical density; The hot isostatic pressing molding comprises: loading the mixed powder into a mold, and using a hot isostatic pressing device to press the mold at 500-800° C. and 100-200 MPa, wherein the density of the pressed blank is ≥90% of the theoretical density.

8. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The silo material should be hot working die steel, preferably H13 steel.

9. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The ratio of the center hole diameter of the grinding head to the target wire diameter is 0.75-0.9, preferably 0.8-0.88, and the center hole diameter of the grinding head is larger than the maximum dimension of the reinforcement phase particles in three-dimensional space.

10. The method for preparing a copper-based composite material wire according to claim 1, characterized in that: The wire should be cooled quickly after extrusion to prevent grain coarsening and oxidation. Inert gas cooling can be used, and the cooling rate should be controlled at 10 2 ~10 4 K / s.